Webholism an investigation on psychological aspects - Bayana Beevi, O. M. S. (Prajyoti Niketan College, Pudukad, Calicut University, 2023)
The present investigation is an attempt to study the psychological aspects of Webholism (internet-dependent behaviour). The broad objectives of the present investigation are: (1) to check the prevalence of Internet Addiction among the Keralite population, (2) to explore Webholism among Internet users, (3) to develop a Digital Detox Experience Test (DDET), (4) to find the relationship between Webholism and psychological variables, (5) to examine the role of sociodemographic variables on Webholism, and (6) to find the predictors of Webholism. To accomplish these objectives, the study used a sequential exploratory research design in which a quantitative study was followed by a qualitative investigation. The study was conducted in three phases. Phase I (Part 1) followed a descriptive research design to assess prevalence, involving 675 internet users in Kerala who were administered Young’s Internet Addiction Test (IAT). Phase I (Part 2) addressed the second and third objectives through an exploratory qualitative study using the Grounded Theory approach. This phase included 289 male and female internet users from Kerala who were asked to switch off their internet for 24 hours and were interviewed the following day about their experiences. Phase II involved test development, revision, and standardization. Phase III was an empirical study conducted to achieve the fourth, fifth, and sixth objectives, involving 1031 adolescents and adults from different districts of Kerala who were administered the study questionnaires. The major findings revealed that the overall prevalence of severe internet addiction was 2%, with 1.71% among males and 0.29% among females. In the absence of the internet, individuals experienced both discomforts and benefits; heavy users reported more discomfort than benefits, whereas lighter users reported more benefits. Webholism was found to be higher among men, the unmarried, students, the unemployed, those living with family, and substance users. Both adolescents and adults use the internet extensively, and no significant difference was found between rural and urban users. Psychological variables such as Type A personality, aggression, psychopathology, procrastination, impulsivity, loneliness, emotion dysregulation, and interpersonal rejection sensitivity were positively associated with Webholism, whereas life satisfaction was negatively associated. Webholism was negatively predicted by need for approval and physical aggression, and positively predicted by limited access to emotion regulation strategies, fragile inner self, anxiety, verbal aggression, non-planning impulsiveness, non-acceptance of negative emotions, attentional impulsiveness, poorly planned goal-directedness, depression, procrastination, and anger.
Keywords: Webholism; Psychological aspects; Digital detox; Adolescents; Adults